Symbiosis of Mutualism in the Transformation of Islamic Law into National Law in Indonesia - Baehaqi, Ja'far (Universitas Islam Negeri Walisongo Semarang, 2021)
The transformation of Islamic law into national law in Indonesia became a trend after the issuance of the Marriage Law and the Religious Courts Law. The transformation of Islamic law is not synonymous with Islamization. If Islamization can occur unilaterally by Islamic law, then this is not the case with transformation. Transformation needs to involve national law as a legal system that overshadows and legitimizes it. Thus there is a dialectical relationship, namely the relationship and interaction between Islamic law and national law in harmony or conflict followed by a settlement in the form of assimilation, accommodation/amalgamation or adaptation. This study finds that philosophically the transformation of Islamic law into national law is closely related to the intersection of the two, namely the transformation of enforcement and regulatory authorities, institutionalization of Islamic law, internal uniformity (unification), Islamization of national law, construction of state law based on non-state law, and legal instrumentalization in national development.Transformasi hukum Islam ke dalam hukum nasional di Indonesia menjadi kecenderungan setelah lahirnya UU Perkawinan dan UU Peradilan Agama. Transformasi hukum Islam tidak identik dengan islamisasi. Jika Islamisasi bisa terjadi secara sepihak hukum Islam, maka tidak demikian halnya dengan transformasi. Transformasi perlu melibatkan hukum nasional sebagai sistem hukum yang menaungi dan melegitimasinya. Dengan demikian terjadi hubungan dialektika, yaitu hubungan dan interaksi antara hukum Islam dan hukum nasional secara harmonis atau konflik yang diikuti penyelesaian dalam bentuk asimilasi, akomodasi/amalgamasi atau adaptasi. Kajian ini menemukan bahwa secara filosofis transformasi hukum Islam ke dalam hukum nasional erat kaitannya dengan persinggungan keduanya, yaitu transformasi penegakan dan otoritas pengatur, pelembagaan hukum Islam, penyeragaman secara internal (unifikasi), Islamisasi hukum nasional, konstruksi hukum negara berbasis hukum non negara, dan instrumentalisasi hukum dalam pembangunan nasional